Autoría en la era de la inteligencia artificial (2024)
This article addresses the growing influence of artificial intelligence (AI) in the writing of academic texts and proposes an authorship scale to assess the AI's contribution at three levels. Through a study involving AI experts and academic evaluation, the challenges in assessing AI-assisted texts, the importance of establishing authorship, and the key principles guiding authorship attribution in this context are examined. The results support the need to address authorship in AI-generated texts.